2015
DOI: 10.3109/09553002.2015.1031850
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a 900 MHz electromagnetic field for 1 hour a day over 30 days does change the histopathology and biochemistry of the rat testis

Abstract: The results show that exposure to 900 MHz EMF causes alterations in adult rat testicular morphology and biochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 43 publications
0
13
0
2
Order By: Relevance
“…Meo et al [ 23 ] reported that exposure to mobile phone radiation for 60 min/day for up to 3 months significantly reduced serum testosterone levels. More recently, Odacı and Özyılmaz [ 24 ] showed that exposure to a 900 MHz electromagnetic field for 1 h/day over 30 days caused bad outcomes in adult rat testicular morphology and biochemistry. In human studies, an obvious decrease in sperm motility in semen samples exposed to a 900 MHz cell phone for 5 min was observed among men [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meo et al [ 23 ] reported that exposure to mobile phone radiation for 60 min/day for up to 3 months significantly reduced serum testosterone levels. More recently, Odacı and Özyılmaz [ 24 ] showed that exposure to a 900 MHz electromagnetic field for 1 h/day over 30 days caused bad outcomes in adult rat testicular morphology and biochemistry. In human studies, an obvious decrease in sperm motility in semen samples exposed to a 900 MHz cell phone for 5 min was observed among men [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the afore mentioned findings, some researchers have asserted that being subject to the non-ionizing radiation emitted by cellular phones has no undesired impacts on the testes and other biological tissues [17][18][19]. The contradictory reports on the effects on testes tissue exposed to non-ionizing radiation emitted from cellular phones determined in previous studies, along with the rapid increase of cellular phone usage, encouraged us to carry out this study.…”
Section: Introductionmentioning
confidence: 87%
“…Rago et al [36] reported a statistically significant relationship between the SAR and oxidative DNA damage biomarker 8-OHdG and DNA fragmentation, after exposure to RF-EMR. Even though there are many similar studies in the literature which report the harmful impacts of cellular phones on reproductive functions, there are also studies which report no impacts on testicles functions [17,37,38]. It is known that degenerative effects such as DNA damage and oxidative stress which may be due to RFR depend on the type of cell and experiment setting (exposure time, frequency, SAR, continuous wave, pulsed wave, being exposed as a cellular phone owner etc.)…”
Section: Analysis Of Tas Tos Osi 8-ohdg and Mdamentioning
confidence: 99%
“…Cincludes that 900 MHz could alter histology, the oxidative status and apoptosis induction in testes. Odaci and Ozyilmaz 2016 [ 22 ] Human spermatozoa (in vitro), n = 26 850 MHz continuous for 1 h; SAR 1.46 W/kg In group 1 of normal sperm, the gene and protein expression of clusterin and DNA fragmentation were increased significantly in EMF exposed sperm. Concluded detrimental effect of mobile phone on sperm parameters.…”
Section: Introduction: History and Sources Of Microwavesmentioning
confidence: 99%